The Determining Factors of Sales Increase in Freight Forwarding Consolidation Goods in Jakarta, Indonesia - Mawariza Pratama, Aftah; Soekirman, Atong; Ricardianto, Prasadja; Farisyi, Sofwan; Arifiani, Librita; Noerkajati, Indang (Dinasti Publisher, 2026)
The main problems in this research were the expensive import shipment service by Non-Vessel Operating Common Carrier (NVOCC) and the poor import cargo service especially in the European and American countries. Meanwhile, this study aims to analyze the main variables such as custom clearance services, trucking services, NVOCC services that affect customer loyalty and customer satisfaction in Freight Forwarding companies. This research used Structural Equation Modelling-SmartPLS3 with the sample as many as 100 customers consisting of forwarders and cargo importers. In general, novelty in research is a new understanding of the factors that affect customer loyalty, especially in the transportation of goods, can also be considered something new. The results of the research data collection, the company needs to maintain and improve the quality of service through marketing strategies with appropriate direct selling statements carried out by the marketing of the Hyper Mega Shipping Company by inviting meetings at the customer's company. This study discusses nineteen hypotheses consisting of six exogenous variables at the port on customer satisfaction and loyalty. The key findings of this study, there are still weaknesses in the process of shipping imported goods, especially in updating the delivery of goods.